Penerapan Model Pembelajaran Cooperative Learning Tipe Snowball Throwing untuk Meningkatkan Sikap Percaya Diri Dan Tanggung Jawab - Krisma Warni; Herman Lusa; Panut Setiono (Universitas Bengkulu, 2023)
This study aims to describe the application of the Snowball Throwing type Cooperative Learning model and increase the self-confidence and responsible attitudes of third-grade students of SD Negeri 02 Kabawetan. This research is classroom action research. The subjects of this study were 16 students consisting of 7 male students and 9 female students. The research procedure is in cyclic form. Each cycle consists of four stages including Planning, implementing actions, observing and reflecting. This research data collection technique using observation techniques. The research instrument was a self-confidence and responsibility observation sheet. The data analysis technique used is the observation sheet using a formula that is processed descriptively, namely quantitative analysis and the range of values ​​for each criterion. The results of this study indicate that the application of the Snowball Throwing learning model has increased from cycle one to cycle two. This can be seen from the increase in students' self-confidence and responsibility. The results of the observation of the assessment of students' self-confidence in the first cycle obtained that 55.30% was included in the sufficient category. Then the increase in the results of the observation of the second cycle was obtained that 75.93% was included in the Good category, while the results of the observation on the assessment of the responsibility of students' attitudes were obtained, namely, 57.98% included in the sufficient category Then the increase in the observation results of the second cycle was obtained that 77.70% was included in the good category. Thus, the application of the Snowball Throwing model can increase the self-confidence and responsibility of third-grade students of Elementary School 02 Kabawetan.